Comment on â€œStatus of Pathology Professionalsâ€ - Jha, R; Shrestha, A; Pant, A; Adhikari, R C; Karki, S (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> In 2012 Jan issue, Journal of Nepal Health Research Council published an article â€œStatus of Pathology Professionalsâ€ by Mishra SK affiliated to Concern for Public Health and Development (C-PHD), Kathmandu, Tiwari BR affiliated to Department of Clinical Microbiology, Peopleâ€™s Dental College, Tribhuwan University and Yadav BK from Department of Clinical Biochemistry, Institute of Medicine, Kathmandu, TribhuwanUniversity, Nepal.As a result, comments were sent to JNHRC, and are published below. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Mishra SK, Tiwari BR, Yadav BK. Status of Pathology Professionals. J Nepal Health Res Counc 2012 Jan;10(20):37-40. PMID: 22929635.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>